1999
DOI: 10.1073/pnas.96.17.9475
|View full text |Cite
|
Sign up to set email alerts
|

Striking activation of oxidative enzymes suspended in nonaqueous media

Abstract: The catalytic activity of four lyophilized oxidative enzymes-horseradish peroxidase, soybean peroxidase, Caldariomyces fumago chloroperoxidase, and mushroom polyphenol oxidase-is much lower when directly suspended in organic solvents containing little water than when they are introduced into the same largely nonaqueous media by first dissolving them in water and then diluting with anhydrous solvents. The lower the water content of the medium, the greater this discrepancy becomes. The mechanism of this phenomen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
66
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(72 citation statements)
references
References 22 publications
4
66
0
2
Order By: Relevance
“…Another general approach is the co-lyophilization of enzyme with molecules such as sugars, alcohols, or polymers that are hypothesized to protect the enzyme against freeze-drying or organic solvents (Dabulis and Klibanov, 1993;Laszlo et al, 2001;Murakami et al, 2001). Other investigators have added small hydrophobic molecules with the idea of protecting the hydrophobic pocket of the enzyme from collapsing (Dai and Klibanov, 1999). Recently, a few groups have shown that crown ethers, oligoamines, and cyclodextrins each are capable of protecting proteases (Broos et al, 1995;Hasegawa et al, 2003;Kudryashova et al, 2003;Montanez-Clemente et al, 2002;van Unen et al, 2002).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Another general approach is the co-lyophilization of enzyme with molecules such as sugars, alcohols, or polymers that are hypothesized to protect the enzyme against freeze-drying or organic solvents (Dabulis and Klibanov, 1993;Laszlo et al, 2001;Murakami et al, 2001). Other investigators have added small hydrophobic molecules with the idea of protecting the hydrophobic pocket of the enzyme from collapsing (Dai and Klibanov, 1999). Recently, a few groups have shown that crown ethers, oligoamines, and cyclodextrins each are capable of protecting proteases (Broos et al, 1995;Hasegawa et al, 2003;Kudryashova et al, 2003;Montanez-Clemente et al, 2002;van Unen et al, 2002).…”
Section: Introductionmentioning
confidence: 98%
“…This process has been optimized for numerous combinations of salts and lyophilization times (Ru et al, 1999(Ru et al, , 2000. Furthermore, the addition of general protectants against protein denaturation during freeze-drying has also been shown to enhance enzyme activity in organic solvents (Dai and Klibanov, 1999;Ru et al, 2001), albeit to a lesser extent than the inclusion of activating salts.…”
Section: Introductionmentioning
confidence: 99%
“…To counter this limitation, many methods have been introduced leading to improved enzyme activity in organic solvents. For example, control of the pH value (Yang et al, 1993), colyophilization with lyoprotectants (Dabulis and Klibanov, 1993) and salts (Khmelnitsky et al, 1994;Ru et al, 1999), addition of water-mimicking agents Kitaguchi et al, 1990), imprinting with substrates and substrate analogs (Rich and Dordick, 1997;Russell and Klibanov, 1988), immobilization (Orsat et al, 1994;Petro et al, 1996;Ruiz et al, 2000), solubilization Okahata et al, 1995a,b;Paradkar and Dordick, 1994;Wangikar et al, 1997;Xu et al, 1997), mutagenesis (Chen and Arnold, 1993), and solvent precipitation (Dai and Klibanov, 1999) represent methods that have been successful for improving the catalytic activity of enzymes. One of the most successful groups of activating additives identified thus far are macrocyclic compounds, which includes cyclodextrins Ooe et al, 1999;Santos et al, 1999) and crown ethers (Broos et al, 1995a;Engbersen et al, 1996;Itoh et al, 1996;Reinhoudt et al, 1989;van Unen, 2000;van Unen et al, 1998van Unen et al, , 2001.…”
Section: Introductionmentioning
confidence: 99%
“…The major problems of 278 substrate solubility and unwanted side reactions promoted by water are also overcome 279 during organic solvent based synthesis. Additionally, in some anhydrous solvents 280 peroxidase (HRP and SBP) activity was actually increased [75], with additional 281 methods, such as salt activation [76] and excipient aided lyophilisation [77] also 282 resulting in increased peroxidase activity. However, in some low water solvents, 283 peroxidases can lose their confirmational structure [78]; although recent advances in 284 peroxidase encapsulation in amphiphilic matrices [79], the use of reverse micelles 285 [80] and oil emulsions [81] allow for peroxidase activity in an extended range of 286 anhydrous solvents.…”
Section: Peroxidase Based Micro-and Nano-systems 219mentioning
confidence: 99%